Figures of Radical Absence Blanks and Voids in Theory, Literature, and the Arts - Irimia, Alexandra-Ecaterina (Culture & Conflict, 2023)
What is there to see in invisible artworks, empty books or blank screens? How do formal absences generate meaning? Constructing an argument by way of montage, the book is an annotated inventory of textual, visual, and conceptual figures of absence. Spanning across media, they reveal a creative tradition that uses absence not as a negative aesthetic category, but as a productive state of radical indeterminacy, with politics and poetics of its own.